Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00280-007-0418-7
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus docetaxel as first-line chemotherapy in patients with advanced non-small cell lung cancer: a lung cancer Galician group phase II study

Abstract: Gemcitabine 1,000 mg/m(2) on days 1 and 8 in combination with docetaxel 85 mg/m(2) on day 8 given in 3-week cycles is an active and well-tolerated first-line chemotherapeutic regimen for advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The every-3-week schedules used consist of docetaxel 75–100 mg/m 2 on day 1 or day 8 and gemcitabine 900–1000 mg/m 2 on days 1 and 8. Response rates of 26–50% and a median overall survival of 7–13 months have been reported in phase II trials [ 19 - 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The every-3-week schedules used consist of docetaxel 75–100 mg/m 2 on day 1 or day 8 and gemcitabine 900–1000 mg/m 2 on days 1 and 8. Response rates of 26–50% and a median overall survival of 7–13 months have been reported in phase II trials [ 19 - 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 314 records dealt with the LC13; however, of these, 74 records were excluded because they did not present original data obtained by means of the module. Consequently, n = 240 articles were considered clinical studies according to our definition and were included in further analyses …”
Section: Resultsmentioning
confidence: 99%
“…ORR , TTP, and OS were 20.4%, 3.6 months, 8.7 months respectively in DG arm versus 31.0%, 5.2 months, 9.4 months, respectively in arm Cis-Gem+Doc (P>0.05). Similarly, the other five phase II trials [17][18][19][20][21] reported no statistical difference in survival between the two regimens.…”
Section: Toxicitymentioning
confidence: 91%